Retracted: A Data Gathering Method Based on a Mobile Sink for Minimizing the Data Loss in Wireless Sensor Networks. (17th April 2014) - Park, Junho; Bok, Kyoungsoo; Seong, Dongook; Kim, Sanglae; Yoo, Jaesoo
The sensor nodes near to the fixed sink node suffer from the quickly exhausted energy. For this, many methods have been researched to distribute the energy consumption into all wireless sensor nodes using a mobile sink. Since the mobile sink changes its location in the network continuously, it has limited time to communicate with the sensor nodes and needs the time to move to each sensor node. Therefore, before the mobile sink approaches the sensor node, the node can collect huge data by event occurrence. It causes the memory overflow of the sensor node and then the data loss. We propose a novel data gathering method based on a mobile sink considering the data loss in wireless sensor networks. The proposed scheme actively sends the stored data to the mobile sink by considering the amount of collected data in the cluster header and the mobile patterns of the sink node. By doing so, it minimizes the data loss of each sensor node. To show the superiority, we compare it with the existing scheme. Our experimental results show that our proposed scheme minimizes the data loss and has similar network lifetime over the existing scheme based on a mobile sink.